Research Trends in K–12 MOOCs: A Review of the Published Literature - Koutsakas, Philippos; Chorozidis, George; Karamatsouki, Angeliki; Karagiannidis, Charalampos (International Review of Research in Open and Distributed Learning, 2020)
Massive Open Online Courses (MOOCs) appeared in the area of educational technologies in 2008. Until 2013, academic research into MOOCs focused mainly on their application to adults as well as students or graduates of tertiary education. However, since 2013, the rising number of K–12 students enrolled in higher education MOOCs made MOOCs a de facto reality in pretertiary education and triggered universities, governments, and MOOC providers to (a) develop MOOCs specifically designed for pretertiary education, and (b) research their potential and value in K–12 educational settings. This resulted in a notable number of K–12 MOOCs and pilot research works in the literature that focused on the potential of MOOCs in compulsory education settings, as well as on their ability to reshape and transform the current educational K–12 framework. This work seeks to (a) trace, analyze, and review the existing literature on K–12 MOOCs,  (b) identify representative MOOC implementations, (c) classify and organize research trends and patterns, and (d) reveal MOOCs’ potential value and impact on K–12 settings. The research used a narrative literature review methodology in order to critically review and qualitatively analyze twenty-one research publications in a systematic manner. Analysis of relevant works demonstrated that MOOCs, under a set of prerequisites, can be effectively incorporated into and positively affect pretertiary education.